بيع العقار على الخريطة في اللائحة السعودية: دراسة فقهية مقارنة - مصطفى، صالح محمد علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The sale of real estate on the map is an innovative way by the owners of real estate investment projects, as a company buys a piece of land, and publishes ads about the desire to put up a project to build housing units, and then provides an opportunity for those wishing to own by selling the property on the map. The research aims to demonstrate the concept of selling the property on the map in the Shari'ah and the Saudi laws, and the statement of the adaptation of the jurisprudence to sell the property on the map, as well as the characteristics of the contract to sell the property on the map in the Shari'ah and the Saudi laws. The researcher used the inductive method in terms of tracking and extrapolation to the question of selling the property on the map. This is done by taking the books that dealt with the subject in the study. Then the researcher went to use the analytical method by listing the existing evidences and discussing what needs to be discussed. He also used the comparative approach for comparing the contracts used for the sale of the property on the map with the similar contracts found in the old Islamic jurisprudence, such as 'Istisna' and Salam, and showing their similarities and differences. At the end of the research, the study concluded that there is a correlation between the sale of istisna and selling the property on the map in terms of application. The study also revealed that selling the property on the map is not a sale of gharar or sale of non-existing things, since Islamic jurisprudence permitted the sale of the non-existing things in two cases: salam and istisna sales. The study showed that the concept of selling the property on the map in the Saudi system is different from other laws.